The Influence Of Parental Knowledge On Oral Habits In Children Aged 7-12 Years In Public Elementary Schools In Cimahi City - Badi Soerachman; Rhabiah El Fithriyah; Hasna Nur Afifah (Sean Institute, 2025)
Bad habits are repetitive actions that typically cease on their own in children under six years old. However, if these habits persist beyond the age of six, they can lead to abnormalities in the dentofacial structure such as malocclusion, facial deformities, and palatal shape irregularities. Knowledge about children's bad habits is crucial for parents as it directly impacts the development and growth of their child's healthy teeth. Insufficient parental knowledge about these habits, if repeated, can result in oral cavity abnormalities in children, which can affect dentofacial functions including speech, tooth occlusion, chewing, swallowing, and aesthetics. Good parental knowledge about the negative impacts of bad habits is essential for parents to take necessary preventive measures. This study aimed to determine the influence of parental knowledge on bad habits in the oral cavity of children aged 712 years in public elementary schools in Cimahi City. The research design used was analytical observational with a cross-sectional approach. The study involved 317 parents of children aged 7-12 years attending public elementary schools in Cimahi City. Data collection was conducted through a 39-item questionnaire distributed via Google Forms. The research findings showed that the correlation coefficient with a significance value (p sig) of 0.000 < 0.05, indicating that there is a correlation between parental knowledge (X) and bad habits in the oral cavity of children (Y). There is an influence of parental knowledge on bad habits in the oral cavity of children aged 7-12 years in Cimahi City.